Analyzing Prepositional Errors in Analytical Exposition Texts of Indonesian EFL Vocational Students - Nur Anisa Lasalutu; Nonny Basalama; Dewi Dama (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study analyzed prepositional errors in texts written by 26 eleventh-grade TKJ students at Vocational High School. Using a descriptive qualitative design, Error Analysis and Surface Strategy Taxonomy classified errors into omission, addition, misformation, and misordering. Data comprised students' texts on the topic 'Smartphones Should Be Allowed in Class' and semi-structured interviews with five students selected from low, medium, and high error levels to explain possible causes. Results showed 98 errors: 92 misformation errors (93.88%) and 6 addition errors (6.12%), while omission and misordering were absent. Misformation dominance indicates that students knew prepositions were needed but struggled to select contextually and collocationally appropriate forms, especially on the internet, focus on, depend on, related to, and impact on. Interviews indicated direct Indonesian translation and confusion over English collocations. The findings suggest contextual, genre-based preposition teaching supported by model texts, collocation practice, and corrective feedback.